The HIV care cascade: Japanese perspectives - Aikichi Iwamoto; Rikizo Taira; Yoshiyuki Yokomaku; Tomohiko Koibuchi; Mahbubur Rahman; Yoko Izumi; Kenji Tadokoro (2017)
Japan has been known as a low HIV-prevalence country with a concentrated epidemic among high-risk groups. However, it has not been determined whether Japan meets the 90-90-90 goals set by the Joint United Nations Programme on HIV/AIDS (UNAIDS)/World Health Organization (WHO). Moreover, to date, the HIV care cascade has not been examined. We estimated the total number of diagnosed people living with HIV/AIDS (PLWHA) (n = 22,840) based on legal reports to the Ministry of Health, Labour and Welfare by subtracting the number of foreigners who left Japan (n = 2,273) and deaths (n = 2,321) from the cumulative diagnosis report (n = 27,434). The number of total undiagnosed PLWHA was estimated by age and sex specific HIV-positive rates observed among first-time blood donors between 2011-2015 in Japan. Our estimates show that 14.4% (n = 3,830) of all PLWHA (n = 26,670) were undiagnosed in Japan at the end of 2015. The number of patients retained in care (n = 20,615: 77.3% of PLWHA), the percentage of those on antiretroviral therapy (n = 18,921: 70.9% of PLWHA) and those with suppressed viral loads (<200 copies/mL; n = 18,756: 70.3% of PLWHA) were obtained through a questionnaire survey conducted in the AIDS Core Hospitals throughout the country. According to these estimates, Japan failed to achieve the first two of the three UNAIDS/WHO targets (22,840/26,670 = 85.6% of HIV-positive cases were diagnosed; 18,921/22,840 = 82.8% of those diagnosed were treated; 18,756/18,921 = 99.1% of those treated experienced viral suppression). Although the antiretroviral treatment uptake and success after retention in medical care appears to be excellent in Japan, there are unmet needs, mainly at the surveillance level before patients are retained in care. The promotion of HIV testing and treatment programs among the key affected populations (especially men who have sex with men) may contribute to further decreasing the HIV epidemic and achieving the UNAIDS/WHO targets in Japan.